Analisis Jaringan Komunikasi Organisasi ASN Terkait Transformasi Birokrasi Di BPSDM Kalimantan Timur - Ependy, Lilin Bayu; Fardila, Ucik Ana (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2024)
Innovation communication in organizations has a significant influence on organizational performance and goals. Communication in the innovation diffusion process is an important part in supporting the acceleration of bureaucratic transformation in government institutions. This research aims to analyze the downward communication network that occurs in ASN at BPSDM East Kalimantan and to analyze the implementation of the diffusion of bureaucratic transformation innovation that occurs at BPSDM East Kalimantan. The research sample was conducted on ASN at BPSDM in East Kalimantan and there were 45 respondents. The research method was carried out using mixed methods. Data was generated using interview and questionnaire techniques, then analyzed using SocNetV v3.1. The research results show that: 1. The structure of the communication network formed is stellar, while the centrality that occurs is fragmented. 2. Implementation of bureaucratic transformation innovation diffusion in East Kalimantan BPSDM includes streamlining echelons, developing competency of apparatus resources and forming KISS for implementing training through Kaltim CorpU.